Further Spread of a blaKPC-Harboring Untypeable Plasmid in Enterobacteriaceae in China - Huang, Jiansheng; Ding, Hui; Shi, Yang; Zhao, Yunan; Hu, Xiaolei; Ren, Jianmin; Huang, Guiying; Wu, Rongzhen; Zhao, Zhigang (Frontiers in Microbiology, 2018)
The wide spread of Klebsiella pneumoniae carbapenemase (KPC)-producing Enterobacteriaceae is great threat to public health in China. Plasmids are among the major factors mediating blaKPC gene dissemination. A total of 156 carbapenem-resistant Enterobacteriaceae (CRE) isolates were identified in a tertiary hospital in China. Six KPC-producing isolates, namely, C. freundii (n=2), E. coli (n=2), E. asburiae (n=1) and C. koseri (n=1), tested positive for the pCKPC18-1-like untypeable plasmid, which was described recently in C. freundii. All 6 plasmids could be easily transferred into E. coli by chemical transformation or conjugation and were confirmed by sequencing to harbor blaKPC-2. Multilocus PCRs and EcoRI-RFLP revealed that the 6 untypeable plasmids belonged to 2 isoforms. High-throughput sequencing of representative plasmids (pCF40 and pEC86) led to the identification of 2 plasmids that shared the common backbone genes repA, DnaJ, StpA and yafB, which were characteristic of the untypeable plasmid, and had similar blaKPC-2 genetic contexts of the Tn3-Tn4401 chimera. Nucleotide comparison revealed high sequence identity of the 2 plasmids with previously reported blaKPC-2-carrying untypeable plasmids. In particular, the pCF40 plasmid from C. freundii and the pHS062105-3 plasmid from K. pneumoniae differed by only 20 single-nucleotide polymorphisms (SNPs). To the best of our knowledge, this is the first report of a blaKPC-harboring untypeable plasmid spread into E. coli, E. asburiae and C. koseri strains in China.